The impact of digitization of airport, asset growth and profitability: A Case Study of PT Angkasa Pura II (Persero) - Masosusa, Desi Rianita; Saefullah, Kurniawan; Rahman, Sulaeman (International Journal for Educational and Vocational Studies)
The purpose of this study is to acknowledge the implementation of digital airport at PT Angkasa Pura II (Persero) and to identify the influence of digital airport investment and asset growth on profitability (ROA) at PT Angkasa Pura II (Persero) a government-owned company. The research method used in this paper is quantitative approach by using multiple regression analysis, using primary and secondary data. The primary data was collected through survey to 100 respondents which are coming from the passengers and employees of the company. Secondary data were obtained from the annual financial and asset reports of PT Angkasa Pura II (Persero). The result reveals that employees and passengers agree towards the digitization of the airport. They were also satisfied with the development of the airports The multiple regression estimation results highlight that airport digitization statistically significant in affecting profitability. The results of statistical tests show that the airport digital variable has a significant effect on profitability, while the asset growth variable has no significant effect on profitability.